Contribution of intragranular misorientations to the cold rolling textures of ferritic stainless steels. (1st January 2020) - Després, A.; Zecevic, M.; Lebensohn, R.A.; Mithieux, J.D.; Chassagne, F.; Sinclair, C.W.
Graphical abstract: Abstract: A combined experimental and simulation study of intragranular misorientation and texture development in ferritic stainless steels is presented. Cold rolling was performed on materials having different grain shapes to reveal variations of misorientations and texture with variations in microstructure. The experimental results were compared with predictions of the Visco-Plastic Self-Consistent (VPSC) model and the recently developed Grain-Fragmentation Visco-Plastic Self-Consistent (GF-VPSC) model. It is shown that the GF-VPSC model, incorporating the development of intragranular misorientations, provides a much better prediction of the texture strength compared to the standard VPSC model. The predictions of intragranular misorientation are also in good agreement with experimental measurements. Both experiments and simulations point to the importance of anisotropy of intragranular misorientation distributions in determining texture development and, importantly, texture strength.